APPLICATION OF MANAGEMENT AND THE ABILITY OF TEACHERS IN IMPLEMENT THE LEARNING IN EARLY CHILDHOOD INSTITUTIONS IN RURAL AREAS (Case studies on early childhood education and early childhood Serbajaman Trieng Village District of North Aceh) - Intan Safiah (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2014)
Establishment of early childhood education in rural areas became a separate phenomenon to the world of education in Indonesia. Visible management and implementation of the learning process is still far from expectations. Therefore, this research aims to describe the: (1) the application of the existing management of early childhood institutions in rural areas, (2) teachers' ability to carry out the process of learning in early childhood institutions in rural areas. This research used a qualitative approach to research types of cases. Sources of data in this research is that there are leaders and teachers in early childhood institutions are used as case study. Data collection techniques are conducted using interviews and observations. Data analysis was performed using qualitative analysis with a systematic set of interview transcripts, observation field notes, and other materials that have been collected. The results obtained: (1) Application of management in early childhood institutions in rural areas, especially early childhood Serbajaman village and early childhood Trieng village districts of Tanah Luas have not yet seen either due to the application of the learning program management, facilities and infrastructure, and public relations management with early childhood. (2) ability to carry out learning in early childhood education teachers in rural areas is still low, because they do not understand the learning model according to the characteristics of early childhood. Not to focus on the principles of learning while playing.  Keywords:    Application of management, the ability of teachers, implementation of early childhood learning institutions, rural areas.